Analyzing the Impact of Inter-smell Relations on Software Maintainability: An Empirical Study with Software Product Lines - Martins, Júlio; Bezerra, Carla Ilane Moreira; Uchôa, Anderson (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
A Software Product Line (SPL) consists of a systematic reuse strategy to construct systems with less effort as long as they belong to the same family that share the same components and belong to the same domain of Marketplace. In this context, to support large-scale reuse, components of a Software Product Line should be easy to maintain. Thus, developers should be more concerned with anomalies known as code smells and more than that, co-occurrences known as Inter-smell deserve to be further studied to verify their real impact on maintainability in SPL. Thus, this paper conducts a study to investigate the impact of Inter-smell occurrences on maintainability in MobileMedia and Health Watcher SPLs. The results show that the presence of co-occurrences of Inter-smell did not negatively impact the maintenance of MobileMedia and Health Watcher SPLs, unlike results found in other studies in the literature, and even more, our results indicate that the metric Lack of Cohesion of Methods is one of the most important for the maintainability of object-oriented SPLs.